1997
DOI: 10.1007/bf02062017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic detection of colorectal cancer cells in circulation and lymph nodes

Abstract: Detection of cytokeratin reverse transcriptase polymerase chain reaction products in the blood and K-ras or p53 gene mutations in the lymph nodes histologically negative for metastasis may be applicable for clinical use, despite some limitations, and may serve as a useful clinical factor for stratifying patients who are at high or low risk for recurrence after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 17 publications
2
21
0
2
Order By: Relevance
“…Five studies were excluded as they were reviews or systematic reviews, which did not report on prognostic outcomes (Tsavellas et al, 2001;Sleijfer et al, 2007;Riethdorf et al, 2008;Sergeant et al, 2008;Tsouma et al, 2008). Ten studies were excluded as they did not report on prognostic outcomes (Denis et al, 1997;Nakamori et al, 1997;Douard et al, 2001;Guadagni et al, 2001;Patel et al, 2002;Silva et al, 2002;Yokoyama and Yamaue, 2002;Schuster et al, 2004;Yeh et al, 2006;Lagoudianakis et al, 2009). The outcomes measured in the 14 studies included in this review were too heterogeneous with regards to the methodology of data collection to allow quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were excluded as they were reviews or systematic reviews, which did not report on prognostic outcomes (Tsavellas et al, 2001;Sleijfer et al, 2007;Riethdorf et al, 2008;Sergeant et al, 2008;Tsouma et al, 2008). Ten studies were excluded as they did not report on prognostic outcomes (Denis et al, 1997;Nakamori et al, 1997;Douard et al, 2001;Guadagni et al, 2001;Patel et al, 2002;Silva et al, 2002;Yokoyama and Yamaue, 2002;Schuster et al, 2004;Yeh et al, 2006;Lagoudianakis et al, 2009). The outcomes measured in the 14 studies included in this review were too heterogeneous with regards to the methodology of data collection to allow quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that changes in expression of CK19 in basal cells are involved in malignant transformation and cancer proliferation. It has been suggested that, clinically, the detection of blood or urinary CK19 in breast cancer 5) , lung cancer 14) , stomach cancer 24) , or colon cancer 11) is useful in the early diagnosis of cancer metastasis. The present results also suggest CK14 and 19 as a potential marker of malignant change in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are classified into two subfamilies: type I acidic (CK9-20); and type II, neutral or basic (CK1-8) 3,4,8) . Cytokeratin 19 is characterized by its expression and localization, and has been utilized as an indicator gene in peripheral blood cancer cells in the diagnosis of breast 5) , lung 14) , stomach 24) , and colorectal cancer 11) . In addition, an attempt was made to evaluate squamous epithelial carcinomas based on localization of CK 10,18) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various methods have been proposed to detect micrometastasis in the dissected lymph nodes. 18,19 Molecular biological techniques, such as immunohistochemical staining and expression of mRNA against cancer-related antigen, have shown that an RT-PCR assay could be one of the most sensitive and accurate methods of detecting cancer cells. [3][4][5][19][20][21] In the present investigation, we used CEA mRNA to detect the spread of epithelial cancer cells.…”
Section: Discussionmentioning
confidence: 99%